Memperkuat Islam Moderat Melalui Metode Pembelajaran Demokrasi di Madrasah Ibtidaiyah - Roihan Imamul M; Ujon Sujono; Yuri A Fathallah (Kopertais Wilayah I DKI Jakarta dan Banten, 2021)
This paper aims to promote the implementation of the concept of strengthening moderate Islam through democratic learning in Islamic elementary schools. The ease of internet access and remote communication, as the effect of globalization in the field of technology, can be used to gain any information needed, including the Islamic knowledge that can be freely learned without teachers. A literature study was employed to describe the data related to the internalization of moderate Islam and democratic learning. The findings demonstrate that moderate Islam (tawasuth) is a life principle that upholds justice in social life. The values of moderate Islam can be internalized in the school curriculum as a reinforcement starting from the elementary school level through implementing democratic learning. This application can be carried out through various methods such as discussion, question and answer, group work, and simulation. The implementation of democratic learning encourages communicative relationships between teachers and students, fosters friendship, and enhances the value of ‘ukhuwah’ (good relations). Furthermore, these methods emphasize student-centered learning. This study also illustrates that democratic learning provides a wide array of opportunities for students to creatively and critically express their ideas and thoughts in their own learning styles.